2011
DOI: 10.1186/1472-6874-11-9
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer screening practices of safety net clinics: Results of a needs assessment study

Abstract: BackgroundFor low income and uninsured populations, safety net clinics are an important source of health care, including preventive services such as mammography screening. However, little is known about how well breast health is coordinated within the safety net clinic environment and what barriers patients encounter.MethodsA needs assessment was conducted among eight community-based safety net clinics located in Montgomery County, Maryland to learn about breast cancer referral and screening procedures. Struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This CME was part of a multi-component program aimed at identifying how community-based health centers (Montgomery Cares) located in Montgomery County, Maryland coordinate care regarding breast health and mammography. Data obtained by medical record abstraction from a needs assessment conducted in Montgomery Cares community health centers revealed that mammography screening rates were low (12%) and that healthcare providers did not regularly recommend mammography screening to their patients [ 27 ]. Therefore, we developed the CME course with the following aims: 1) to increase awareness about breast cancer morbidity and mortality; 2) to increase healthcare providers understanding of factors that influence decision to undergo breast cancer screening; 3) to elucidate how culture and cultural competence can influence breast cancer services; and 4) to develop skills that healthcare providers can use to help recommend breast cancer screening to women of diverse backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…This CME was part of a multi-component program aimed at identifying how community-based health centers (Montgomery Cares) located in Montgomery County, Maryland coordinate care regarding breast health and mammography. Data obtained by medical record abstraction from a needs assessment conducted in Montgomery Cares community health centers revealed that mammography screening rates were low (12%) and that healthcare providers did not regularly recommend mammography screening to their patients [ 27 ]. Therefore, we developed the CME course with the following aims: 1) to increase awareness about breast cancer morbidity and mortality; 2) to increase healthcare providers understanding of factors that influence decision to undergo breast cancer screening; 3) to elucidate how culture and cultural competence can influence breast cancer services; and 4) to develop skills that healthcare providers can use to help recommend breast cancer screening to women of diverse backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…The current study shows that in 2016 and 2017, most women visited a screening centre through referrals (20.6% and 18.9%, respectively (Table 3). Women unaware of the screening program mostly use the effective referral process [23] . From another perspective, a high referral rate indicates a low awareness among women about the screening program.…”
Section: Resultsmentioning
confidence: 99%
“…For example, similar to non-federally funded safety net clinics, FQHCs often lack the specialized staff and refer patients off-site for their follow-up care (5,33). However, this referral process can often be impeded by patient characteristics such as SES (5,34,35).…”
Section: Discussionmentioning
confidence: 99%